Educação ambiental e desenvolvimento de práticas pedagógicas: um olhar voltado para os trabalhos dos docentes e discentes do Centro de Ensino Gardner, em Canto do Buriti - Piauí - Lima, Maria dos Remédios Regina de Jesus (Universidade do Vale do Rio dos Sinos, 2021)
The challenges of the contemporary world make it increasingly necessary to reflect on the way Environmental Education (EE) can contribute to conscientious practices of preservation and rational use of the natural resources, which are so essential for the maintenance of ecosystems. In this regard, this study had as general objective to understand the development of transversal pedagogical practices regarding Environmental Education in the Centro de Ensino Gardner (CEG), in Canto do Buriti – Piauí. The theoretical background was based on the perspective of Paulo Freire‟s critical pedagogy, specifically concerning educational questions related to EE; as well as on contributions from authors who defend the adoption of a critical and participatory Environmental Education, such as Giron and Ferraro, Medina and Santos, Dias, Cascino, Reigota, Barcelos, and Figueiredo. Semi-structured interviews were conducted with three teachers and four students from the 5th year of elementary education. The documents selected for analysis were the CEG‟s PoliticalPedagogical Project (PPP) and the three teachers‟ lesson plans. The results related to the analysis of the PPP show that only one brief excerpt of the document, in the Health of the Environment subtopic, briefly mentions EE. Regarding the results of the analysis of the interviews with the teachers, it was observed that the participants demonstrate to know the need and the importance, in pedagogical practices, of environmental issues, and demonstrate to know the concepts of transversality and interdisciplinarity. However, although they state that they teach classes about the subject, it was possible to observe that the EE-related practices occur on an ad hoc basis. In addition, in the analysis of their pedagogical practices, it was clear that the involvement of the teachers with EE is only occasional, and there are gaps regarding the insertion of environmental issues as transversal topics in the different areas of knowledge. In turn, in the students‟ responses, it was possible to note that they already internalized the importance of issues related to the preservation of the environment and the grave consequences that pollution provoked by humankind has caused to the planet and, consequently, to human beings. However, their interviews highlight that the EE classes taught by teachers at the school are connected to the period of celebration dates related to the environment. Therefore, the study emphasizes that the insertion of Environmental Education in pedagogical practices is, without a doubt, a challenge regarding the way of transversally conceiving it in schools.
Keywords: Educação ambiental; Práticas pedagógicas; Transversalidade; Environmental education; Pedagogical practices; Transversality; ACCNPQ::Ciências Humanas::Educação